Revisión y mejora del Sistema de Contratación Administrativa del Departamento de Obras por Contrato del Ministerio de Obras Públicas y Transportes de Costa Rica - Oguilve-Pérez, Jorge Baruch (Instituto Tecnológico de Costa Rica, 2006)
Public bid constitutes the ideal and imperative mean in which public institutions, non-governmental entities, public companies, private enterprises and individuals, that use total or partial public funds, obtain goods and services to accomplish their goals. To act accordingly with what is established by law (Ley de Contratación Administrativa No. 7494) and its policies, these institutions employ different technical and legal instruments to obtain the corresponding supplying. Therefore, these instruments must be clear and concise for the Bidders to effectively understand governmental requirements. In the case of estate building, the importance of the understanding of these requirements is that they influence the Bidders’ charge. For this matter, relevant documents are made to define the expected characteristics of the service or product as follows: 1) Scope of Bid 2) Technical specifications 3) Project budget information Due to recurrent discrepancies and the government and bidders financial lost it is urgent for these documents to be meticulously checked in order to create a parallelism between them and the law, leading to an accurate interpretation. To fulfill this need, this project proposes adjustments, spread of the fundamental principals of bidding and actualization of the technical specifications and realistic estimations.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica.Escuela de Ingeniería en Construcción, 2006.
Keywords: Especificaciones; Presupuesto; Planificación; Control; Diagnóstico